Neurocognitive Profiles in Duchenne Muscular Dystrophy and Gene Mutation Site - D’Angelo, Maria Grazia (Elsevier Science Publishing, 2011)
The presence of nonprogressive cognitive impairment is recognized as a common feature in a substantial proportion of patients with Duchenne muscular dystrophy. To investigate the possible role of mutations along the dystrophin gene affecting different brain dystrophin isoforms and specific cognitive profiles, 42 school-age children affected with Duchenne muscular dystrophy, subdivided according to sites of mutations along the dystrophin gene, underwent a battery of tests tapping a wide range of intellectual, linguistic, and neuropsychologic functions. Full-scale intelligence quotient was approximately 1 S.D. below the population average in the whole group of dystrophic children. Patients with Duchenne muscular dystrophy and mutations located in the distal portion of the dystrophin gene (involving the 140-kDa brain protein isoform, called Dp140) were generally more severely affected and expressed different patterns of strengths and impairments, compared with patients with Duchenne muscular dystrophy and mutations located in the proximal portion of the dystrophin gene (not involving Dp140). Patients with Duchenne muscular dystrophy and distal mutations demonstrated specific impairments in visuospatial functions and visual memory (which seemed intact in proximally mutated patients) and greater impairment in syntactic processing.